Physicochemical Properties and Biodegradability of Biofilm Based on Taro Starch and Duck Bone Gelatin - Laksanawati, Trias Ayu; Khirzin, Muhammad Habbib; Amaniyah, Maghfirotul; Meidayanti, Karina; Deva, Bella Diah (Universitas Jenderal Soedirman, 2024)
Biofilm is an environmentally friendly plastic that is easily biodegradable. However, not all biodegradable plastics have the desired properties for packaging because they are made from renewable natural materials. The biofilm in this study was made from renewable natural raw materials that had never been used before, namely taro starch and duck bone gelatin. Mixing the two materials improve their physical properties and biodegradabilily This study was to to investigate the effect of adding duck bone gelatin 0%, 5%, 15%, 25% and 35% on physicochemical properties, namely color, oxygen permeability, and metal content (Pb and Cd) as well as biodegradability of biofilms. The method used in this research was solution casting. The results obtained from the color parameter with the highest lightness (L) value were produced in the addition of 15% of 85.26, for the highest value of color a was produced in the addition of 0%, namely 0.94, and the value of color b with the addition of 35% resulted in the highest color value of 1.67. The highest percentage of biodegradability was produced on day 14 with the addition of 35% duck bone gelatin in compost soil to produce a percentage of 100%, while for barren soil the yield was 54.54%-66.66%. The content of Cd and Pb in the biofilm is below the SNI limit. Biofilm is impermeable which can be used as food packaging. Keywords: Biodegradability, biofilm, gelatin, physicochemical, starch